Produksi Sosial dalam Peta Pemikiran Janet Wolff dan Contoh Penerapannya dalam Kajian Filologi - Windayanto, Riqko Nur Ardi; Santoso, Widjajanti Mulyono (Jumantara: Jurnal Manuskrip Nusantara, 2024)
This article aims to map the social production theory conceptually by Janet Wolff and its application in philological studies by taking the Hikayat Indraputra as an example of an object of analysis. Conceptually and analytically social production theory covers the aesthetic codes that set the literature, the ideology, the cultural production aspects, and the meaning as optional discussion. In this theory, the manuscript which consists of literature text is understood as a social product or collective product so that the analysis relates the text and manuscript, the text and context, and the textological analysis and codicological analysis. Methodologically this theory is applied, especially, by using the dialectical method that by Wolff is built on historical materialism. Manuscripts and texts are very diverse. Therefore, using this theory requires certain adjustments to the manuscripts and texts to be studied so that the theory is not applied haphazardly. Ultimately, with its broad concept offering, this theory can be used to carry out one of the tasks in philological studies, namely interpreting or interpreting edited text, and continuously developing the philological studies.